Peran Pendidikan Kewarganegaraan dalam Meningkatkan Kesadaran dalam Sekolah Dasar - Alysa Humairah Afkar (STIKes Ibnu Sina Ajibarang, 2025)
This study examines the strategic role of Civic Education (PKn) in increasing national and state awareness among elementary school students in Indonesia. Through a qualitative approach with conceptual analysis methods and literature studies, this study identifies four main roles of civil society: the cultivation of national identity, the recognition of citizens' rights and obligations, the development of democratic values, and the formation of attitudes of tolerance and multiculturalism. The dimensions of consciousness developed include constitutional consciousness, nationalism, multiculturalism, and participatory. This article also explains effective PKn implementation strategies through experiential learning, integration with daily life, the use of interactive learning media, and example and habituation. Despite having a vital role, the implementation of PKn still faces challenges in the form of learning that tends to be theoretical, limited teacher competence, and counterproductive environmental influences. The evaluation of PKn's success in increasing awareness can be measured through behavior change, conceptual understanding, active participation, and social concern of students. In conclusion, PKn that is implemented contextually and meaningfully from an early age can be an effective foundation in forming good citizens and maintaining national identity in the global era.